Shorebirds: Threats and Strategies for Conservation - Mhatre, Manda Anil (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Shorebirds or waders inhabit in the coastal littoral zone and play critical role in the marine ecosystems and environmental monitoring. Ecological services provided by shorebirds include facilitating energy and nutrient transfer; enrich soils to increase biodiversity along with primary and secondary production. Shorebirds are used as indicators of pollution, environmental change, food chain, and climate change. These birds are vulnerable to hunting pressure, habitat changes, disturbance and other threats. Disturbance to roosting or feeding shorebirds is a major concern along coastlines. Shorebirds can adapt to regular disturbances at predictable distances; but some loud, unpredictable disturbances such as shouting, people running, jet skis, helicopters, kite boards, fast and noisy boats, and dogs are the most threatening to them. Anthropogenic stressors such as chemical pollution, fishing, habitat loss, invasive alien species/introduced species, marine debris, oil spills, poaching, and shipping pose threats to the shorebirds. Human activities can affect the shorebirds, either directly or by producing behavioural or physiological impacts. Present review attempts to provide an illustrative and updated account of shorebirds relevant to current status; natural, anthropogenic, and emerging and under-studied threats; and strategies to be adopted for better conservation and restoration of shorebirds. This study suggests that about threats to shorebirds, future research priorities should be given to assess the cumulative effects of anthropogenic stressors on shorebirds and to recommend effective preventive measures.